Latest Developments in 4th generation district heating and smart energy systems - Østergaard, Poul Alberg; Johannsen, Rasmus Magni; Lund, Henrik; Mathiesen, Brian Vad (International Journal of Sustainable Energy Planning and Management, 2021)
This editorial introduces the 31st volume of the International Journal of Sustainable Energy Planning and Management. This volume reports some of the latest developments in energy systems analyses of smart energy systems and of district heating as well as in methods and analyses using multi-objective optimisation. In one of the analyses, the authors investigate the effects of decentralised storage in district heating systems, finding positive effects on grid design as the impact of peaks can be reduced. Three contributions address the more sociological factors influencing acceptance and energy system development such as ownership, awareness, and moral.